(untitled) (Journal of Pharma Insights and Research, 2025)
The Gossypium genus, the source of commercial cotton, holds a significant, often-overlooked position in global ethnomedicine. While its economic value is dominated by fiber production, various parts of the cotton plant, including seeds, roots, leaves, and flowers, have a long history of use for treating a spectrum of ailments. The genus is a rich reservoir of bioactive constituents, most notably the polyphenolic sesquiterpenoid aldehyde gossypol, alongside a diverse array of flavonoids, phenolic acids, peptides, and proteins. These compounds contribute to a broad spectrum of biological activities. Scientific validation has increasingly substantiated the plant’s traditional applications, revealing potent anticancer, antiprotozoal, antimicrobial, antioxidant, and anti-inflammatory properties. Gossypol, in particular, has been extensively studied as a multi-target anticancer agent. Moreover, constituents from Gossypium species and the cellulose backbone itself are being leveraged in novel material science applications, including functionalized antimicrobial textiles and advanced nanocrystal-based drug delivery systems. This review collates the ethnobotanical context, details the main phytochemical classes, organizes the current pharmacological evidence, and discusses the critical toxicological and sustainability considerations, indicating that the Gossypium genus as a valuable resource for modern therapeutic and biotechnological development.